COLLABORATIVE GOVERNANCE IN EDUCATION CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAMS IN PAHAE JULU, NORTH TAPANULI REGENCY, NORTH SUMATERA PROVINCE - Sitompul, Gunadi Franyadi; Athahirah, Astika Ummy (Jurnal Politik Pemerintahan Dharma Praja, 2022)
The Pahae Julu District's Education CSR initiative is a form of collaboration between stakeholders to overcome limited resources to improve education quality, which is still deemed low. This research aims to gain an overview of government collaboration in the education sector through the execution of CSR initiatives, implementation difficulties and efforts to overcome them in Pahae Julu District. This research used a quasi-qualitative research method. Interviews, observation, and documentation were data collection procedures that used data triangulation techniques. Data reduction, data presentation, and conclusion drafting were data analysis approaches. According to the findings of this research, the Government Collaboration on the Implementation of the Educational Corporate Social Responsibility (CSR) ran smoothly before 2020, but several programs were hampered and temporarily suspended due to the Covid-19 pandemic in 2020. However, the government, corporation, and community will continue to work together to maximize this collaboration for mutual prosperity, particularly in improving educational quality, strengthening commitment by creating program designs and efforts to mobilize common interests, developing a plan for setting standards (indicators of success) to facilitate evaluation, and anticipating inhibiting factors that become obstacles by increasing community participation. Keywords: Collaborative Governance, Corporate Social Responsibility, Education